El alcance de la normativa legal ecuatoriana y el impacto del malware en la seguridad cibernética. - Changoluiza Fonseca, Kateryn Verónica (2024)
The present research was developed in the order to understand, through an analytical, doctrinal and comparative legal study, the scope of Ecuadorian legal regulations and the impact of malware on cyber security, to determine the difficulties in the investigation of computer or cybercrimes. The study has been developed through a type of descriptive, pure and historical legal research, with a non-experimental design, which has taken as a sample of four provincial prosecutors of Chimborazo and one computer expert accredited by the “Consejo de la Judicatura” from Quito. The data collection technique called interview was applied and two interview guides were used as instruments, which have allowed to explain the perception of the prosecutor about the effectiveness of the Ecuadorian regulations against computer crimes committed through the use of malware, and to understand the role of computer experts in the investigation of the technical operation of malware as a tool to commit computer crimes that affect cybersecurity. In addition, a documentary analysis was conducted using a matrix as a data collection instrument, through which news from the national media about the most influential malware attacks in the country were recorded. As a result of the interviews, four of the five interviewees revealed that Ecuadorian regulations are insufficient and generalist to address computer crimes. They conclude that there is a lack of international cooperation agreements, specific typification of the new criminal behaviors in cyber-attacks and non-existent regulation of manuals and protocols of investigative procedures between prosecutors and judicial police specifically for the investigation, storage and compilation of digital evidence in malware cases. Therefore, the alternative hypothesis is accepted, and it is affirmed that the updating of the cybersecurity regulation will allow the effective investigation of computer crimes committed with malware.